The Role of Job Engagement in Mediating Work Life Balance in Turnover Intention - S, Aynul Musthofa; Suaedi, Falih (Ekonomis: Journal of Economics and Business, 2024)
Gen Z is a generation that has difficulty experiencing job satisfaction. Gen Z tends to have the intention to reach the highest peak in a job. Therefore, Gen Z has a tendency to leave the company and look for alternative jobs in other workplaces. This study aims to determine the effect of work life balance on turnover intention through job engagement for Gen Z employees in Surabaya. This research method uses quantitative analysis techniques to test hypotheses and test mediation or path analysis. The results of this study found that work life balance and job engagement have a simultaneous effect on turnover intention variables.